Business Opportunities and Challenges for the Millennial Generation in the Socio-Economic Aspects of the Industrial Revolution 4.0 - Afiyanta wulandari; Abdur Rohman (Managing: Jurnal Bisnis dan Manajemen, 2025)
Currently, Indonesia is facing the era of Industrial Revolution 4.0, where business supply chains are digitally connected, which has an impact on simplifying the supply chain. This research uses qualitative methods and focuses on literature study. The results of this research show the rapid development of the business world, especially MSMEs and creative businesses that utilize digital technology in Indonesia. The era of the Industrial Revolution 4.0 for the creative and innovative millennial generation is both an opportunity and a challenge in running a business in Indonesia. The government's role is very crucial in building an ecosystem that supports and provides adequate facilities in the form of regulations and technological facilities for the growth of MSMEs and creative businesses in Indonesia.